Relationship between healthy diet and prevalence of obesity among adults - Annisa Andriyani; Erny Elviany Sabarudin; Fitri Ardiani; Jean Henry Raule (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the relationship between healthy eating and the prevalence of obesity in adults, with reference to various literature studies. Obesity has become a significant global health problem, which is associated with an increased risk of chronic diseases such as type 2 diabetes, hypertension, heart disease, as well as some types of cancer. Furthermore, obesity also contributes to physical and cognitive disabilities in adults, especially among older adults. Although weight loss can reduce this risk, there are concerns among healthcare providers about the potential risks that can arise from weight loss, such as loss of muscle mass and bone density. Intentional weight loss has been shown to be effective in improving glycemic control, reducing cardiovascular risk factors, and improving physical function, but it should be done with close supervision. A healthy diet, including a balanced intake of macronutrients, as well as essential micronutrients such as vitamins D and B-12, is essential in reducing the prevalence of obesity and maintaining a healthy body. The study emphasizes the importance of health policies that strengthen access to nutritious food and educational programs that focus on dietary changes and increased physical activity